Experimental and numerical study of the effects of heave plate on the motion of a new deep draft multi-spar platform - Li, Binbin (2013)
The heave motion of a floating structure is critical, as a favorable heave characteristic permits dry tree systems, amongst other benefits. The heave response can be suppressed by installing heave plates. However, the associated hydrodynamic effects, which include viscous damping and added mass, are very complicated. Moreover, there are limited experimental investigations to understand the heave plate effects on actual platform designs. This paper aims to study the abovementioned issue based on a novel deep draft multi-spar (DDMS) platform, for four different configurations (with/without upper and lower heave plates). A set of experiments (free decay, regular and irregular wave tests) are conducted, and compared with time domain and linearized frequency domain analyses. Amongst other things, the investigations and discussions include the added mass and damping coefficients for the platform and heave plates, comparison of experimental and numerical results, and the influence of the heave plates on the surge, heave and pitch motions.